Arthrosonography as a method of assessment of xefocam efficacy in rheumatoid gonitis - E S Much; O V Pushkova; Т П Федина; R M Balabanova (Научно-практическая ревматология, 2004)
Arthrosonography of 74 knee joints performed in 37 pts with rheumatoid arthritis before treatment with xefocam (Nicomed) in 34 revealed signs of intra and extra-articular inflammation with presence in 100% fluid in fore part of the joint, increase B. Suprapatellaris size and thickening of synovial membrane. Fluid in lateral parts was revealed in 33 joints and in back part - in 22 joints. Semimembranosus muscle tenosynovitis was revealed at 22 joints. After xefocam administration (intra-articular injections 8 mg once a week for 3 weeks) signs of intra-articular inflammation decreased in 28 and extra-articular - in 21 joints. So xefocam provides anti-inflammatory effect and can be used for treatment of synovitis.